Cognitive Balance of Students in the Kindergarten department (Journal Of Educational and Psychological Researches, 2023)
AbstractBalance is a psychological need and a requirement of importance as the individual seeks to maintain it.  The research problem is summarized in the question: do students in the kindergarten department have a cognitive balance? The research aims to identify the cognitive balance of students in the kindergarten department and to identify if there are differences among students of the four stages according to the cognitive balance. The research community was limited to the students in the kindergarten department at the University of Baghdad / College of Education for Women and Al-Mustansiriya University / College of Basic Education and Iraqi University / College of Education for Women for the academic year 2021-2022. To achieve the objectives of the research, the two researchers developed a cognitive balance scale of (23) items with five alternatives that are (applies to me, applies to me often, applies to me sometimes, applies to me rarely, does not apply to me) with weights (1, 2, 3, 4, 5). The scale proved good validity and reliability. The scale was applied to a sample of (300) female students from the Kindergarten Department were chosen randomly, the findings of the study revealed that the female students of the kindergarten department, in general, have a good cognitive balance, all female students of the department have approximately an equal cognitive balance in all stages. Lastly, the researchers presented a set of recommendations and suggestions.